ANALYSIS OF THE INFLUENCE OF INTELLECTUAL CAPITAL ON FINANCIAL PERFORMANCE IN THE BANKING INDUSTRY IN INDONESIA BASED ON CORE CAPITAL GROUPS - Pangestu, Ardi; Muharam, Harjum (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2023)
This study examines influenceintellectual capitalon financial performance in the banking industry in Indonesia based on core capital groups. Intellectual capitalIn this research, Human Capital Efficiency (HCE), Innovation Capital Efficiency (INVCE) and Capital Employed Efficiency (CEE) are used as independent variables. Financial performance in this research uses the NPL, CKPN, CAR, ROA and BOPO ratios as dependent variables. The research sample isdata on intellectual capital, NPL ratio, CKPN, CAR, BOPO and CKPN for 94 (ninety-four) commercial banks in Indonesia as of June 2022 which are divided into 4 (four) groups based on KBMI. There are 62 (sixty-two) KBMI-1 banks, 16 (sixteen) KBMI-2 banks, 12 (twelve) KBMI-3 banks, and 4 (four) KBMI-4 banks. The research period is divided into 2 (two) periods, namely before the Covid-19 pandemic (January 2013 to December 2019) and the Covid-19 pandemic period (January 2020 to June 2022). Data analysis uses regressionmultiple or Multiple Regression Analysiswith the help of Eviews software. The research results showed that in KBMI-1 there were 5 hypotheses accepted and 10 hypotheses rejected in the period before Covid-19, while in the Covid-19 period there were 9 hypotheses accepted and 6 hypotheses rejected. KBMI-2 had 8 accepted hypotheses and 7 rejected hypotheses in the period before Covid-19, while in the Covid-19 period there were 7 accepted hypotheses and 8 rejected hypotheses. KBMI-3 had 10 accepted hypotheses and 5 rejected hypotheses in the pre-Covid-19 period, while in the Covid-19 period there were 9 accepted hypotheses and 6 rejected hypotheses. Finally, in KBMI-4 there were 11 accepted hypotheses and 4 rejected hypotheses in the period before Covid-19, while in the Covid-19 period there were 5 accepted hypotheses and 5 rejected hypotheses